2000
DOI: 10.1103/physrevb.61.11340
|View full text |Cite
|
Sign up to set email alerts
|

Proximity effects and Andreev reflection in a mesoscopic SNS junction with perfect NS interfaces

Abstract: Low temperature transport measurements on superconducting film-normal wire-superconducting film (SNS) junctions fabricated on the basis of thin superconducting polycrystalline PtSi films are reported. Due to the perfectness of SN boundaries in the junctions, zero bias resistance dip related to pair current proximity effect and subharmonic energy gap structure originating from phase coherent multiple Andreev reflections have been observed and studied. 74.80.Fp, 74.50.+r Research activity in the study of pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…(15) numerically and found that the first fold-bifurcation appears at E c ≈ 5E Th /L rather than ≈ 49E Th /L found in Eq.(3). We thus have demonstrated that even in case of large fluctuations, where the extension beyond the linear approximation is required, the bifurcation of the fluctuation spectrum pre- The details of the system preparation are given in [15]. The right inset displays the full set of the differential resistance vs. V dependences at different temperatures given in mK in the legend.…”
mentioning
confidence: 84%
“…(15) numerically and found that the first fold-bifurcation appears at E c ≈ 5E Th /L rather than ≈ 49E Th /L found in Eq.(3). We thus have demonstrated that even in case of large fluctuations, where the extension beyond the linear approximation is required, the bifurcation of the fluctuation spectrum pre- The details of the system preparation are given in [15]. The right inset displays the full set of the differential resistance vs. V dependences at different temperatures given in mK in the legend.…”
mentioning
confidence: 84%
“…The ZBCP has been reported in various S-N hybrid structures, 15,20,[32][33][34][35][36] but its physical origin is still under debate. The ZBCP can be induced by the pair current across superconductor-semiconductor interfaces.…”
Section: (D)mentioning
confidence: 99%
“…The similar set of parameters corresponds, for example, to the 3nm-thick PtSi film studied in [6], [7].…”
mentioning
confidence: 99%